Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4103/jisp.jisp_265_15
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced gingival overgrowth: A critical insight into case reports from over two decades

Abstract: Drug-induced gingival overgrowth (DIGO) is a well-recognized adverse effect of certain systemic medications. Calcium channel blockers, anticonvulsants, and immunosuppressants are frequently implicated drugs in the etiology of DIGO. Drug variables, plaque-induced inflammation, and genetic factors are the three important factors in the expression of gingival changes after systemic medication use. Careful clinical examination and thorough history taking form the basis for diagnosis of DIGO. Histopathological exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…[ 1 6 7 ] Furthermore, Samudrala et al . [ 11 ] in a 2017 review suggested certain features to be generally more frequent in DIGOs. These include the initiation of GO within 3 months of drug use, frequent occurrence in the anterior gingiva in younger age groups, and a lack of association with attachment loss.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 1 6 7 ] Furthermore, Samudrala et al . [ 11 ] in a 2017 review suggested certain features to be generally more frequent in DIGOs. These include the initiation of GO within 3 months of drug use, frequent occurrence in the anterior gingiva in younger age groups, and a lack of association with attachment loss.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have implicated nifedipine and amlodipine as the frequent causes of GO,[ 2 4 11 15 16 17 18 19 20 ] though this unwanted effect has also been reported in patients taking verapamil. [ 21 ] The recent case reports’ review by Samudrala et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histologically, there is presence of sparse to moderate inflammatory cell infiltrate correlated to inflammatory condition. A recent study stated that it is not clear whether plaque is a cause or a result of GO 16. Another reason why some patients have greater cellular proliferation and collagen synthesis may be attributed to the variation in the differential subpopulations of fibroblasts inthe individuals.…”
mentioning
confidence: 99%